2004
DOI: 10.1542/peds.113.2.406
|View full text |Cite
|
Sign up to set email alerts
|

Management of a Severe Carbamazepine Overdose Using Albumin-Enhanced Continuous Venovenous Hemodialysis

Abstract: Carbamazepine intoxication is common in the pediatric population. Highly protein-bound, carbamazepine is not removed efficiently through conventional hemodialysis. We describe the use of albumin-enhanced continuous venovenous hemodialysis (CVVHD) in a 10-year-old girl who developed coma and respiratory depression due to an intentional carbamazepine overdose (peak drug level of 44.8 microg/ml; therapeutic range: 8-12 microg/ml). Without intervention, the half-life of drug elimination is 25 to 60 hours in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 16 publications
1
54
1
Order By: Relevance
“…Albumin-enhanced dialysate has been reported in one case to treat a 6.5-month-old with valproic acid toxicity and a carbamazepine overdose in a 10-year-old 10,11 .Theophylline is approximately 50-60% protein bound and under normal conditions metabolized by the p450 enzyme in the liver 12 . For these reasons, we did not add albumin to the dialysate fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Albumin-enhanced dialysate has been reported in one case to treat a 6.5-month-old with valproic acid toxicity and a carbamazepine overdose in a 10-year-old 10,11 .Theophylline is approximately 50-60% protein bound and under normal conditions metabolized by the p450 enzyme in the liver 12 . For these reasons, we did not add albumin to the dialysate fluid.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to the dose of albumin, one case report showed that dialysate albumin as low as 1.85% resulted in similar removal of bilirubin when compared to 5% [71]. Finally, SPAD was reported to increase the elimination of albumin-bound drugs especially with the presence of AKI that would reduce their renal drug elimination [72,73,74]. The in-vitro study by Churchwell et al [74] was the most controlled as it compared the effect of various blood flows (180-270 mL/mn), dialysate flows (1-4 L/h), dialysate albumin concentrations (0, 2.5, and 5%), and dialyzers (1.5 m 2 polysulfone and 0.6 m 2 acrylonitrile 69) on the clearance of phenytoin, valproic acid, and carbamazepine.…”
Section: Extra-corporeal Liver Supportmentioning
confidence: 99%
“…Acute drug intoxications and hyperammonemia secondary to inborn errors of metabolism are best treated with IHD since rapid drug removal is important to prevent morbidity and IHD is the most efficient RRT modality [122,123]. However, CRRT can be very effective for protein-bound drug removal if albumin is added to dialysis fluid and acute serum ammonia reduction in inborn errors of metabolism if higher than usual CRRT doses are used [124][125][126]. Finally, the particular center's expertise and nursing support availability should play a major role in determining the optimal RRT modality.…”
Section: Modality Choicementioning
confidence: 99%